Strategies of IT Companies in South Africa during the 2008/2009 Recession - Dias, Yvonne Maria (My University, 2012)
This study seeks to gain a better understanding of the impact of the recession on the strategies of IT companies in South Africa. This was determined by means of a literature review covering strategies that organisations could utilise during recessions as well as non-recession periods. In addition, the concept and impact of a recession were explored. The problem statements outlined in the literature review aimed to answer the following questions: What strategies were employed by organisations before the recession? What changes were made, if any, to their strategies during the recession? And lastly, what was the financial impact of the recession on these organisations? The research was conducted with a targeted group of Managing Directors (MD’s), Directors and senior staff who deal directly with the strategies of various IT companies in South Africa. Owing to the limited number of listed IT companies on the JSE, the sample included listed companies and medium-sized organisations. In addition, the study was not limited to one area of IT but covered organisations involved in the selling of hardware and software and offering development services. The results of the study showed that prior to the recession, most of the organisations were on a growth path and many where focused on acquisitions. In addition, cost control appeared not to be a major priority. However, the recession forced all organisations to change the way they interacted with clients, which involved forming long-term relationships. In addition, the recession forced organisations to implement cost control measures that would also be sustainable once out of the recession. A set of recommendations was compiled based on the research findings and further areas of research were highlighted
MBA thesis - WBS
Keywords: Informaton technology companies; Recessions